Continuous Cropped Winter Wheat in Central Kansas - Warmann, Gerald W. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on continuous cropped winter wheat production in central Kansas.
MF574_1995_10
Keywords: MF574; Economics; Crops; MF